2016
DOI: 10.3991/ijet.v11i07.5889
|View full text |Cite
|
Sign up to set email alerts
|

Visualizations of Online Course Interactions for Social Network Learning Analytics

Abstract: Abstract-Social network learning analytics aims to extract useful information to improve the learning process, but the variety of learning management systems makes this task burdensome and difficult to manage. This study shows how Gephi, a general-purpose, open-source social network analysis application, can be used by instructors and institutions to extract and visualize relevant information that is commonly hidden or difficult to observe for course coordinators and teachers. The empirical case study uses dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…Gephi is an open-source software programme that plots visual representations of social networks through maps and graphs. It can also calculate SNA parameters and the ranking, partitioning and filtering of nodes and ties (Bozkurt et al, 2016;Hernández-García et al, 2016). In SNA each actor is regarded as a node or a vertex in the overall network, and the various relationships occurring between actors are links, ties or edges connecting actors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gephi is an open-source software programme that plots visual representations of social networks through maps and graphs. It can also calculate SNA parameters and the ranking, partitioning and filtering of nodes and ties (Bozkurt et al, 2016;Hernández-García et al, 2016). In SNA each actor is regarded as a node or a vertex in the overall network, and the various relationships occurring between actors are links, ties or edges connecting actors.…”
Section: Discussionmentioning
confidence: 99%
“…One instructive observation from this this study is that significant but low relationship was found between the number of times students read or replied to messages and academic performance. Among other things, this tends to emphasise one of the benefits Gephi has as a social network tool that can be used to visualise not only student participation but student engagement as well within OLEs (Hernández-García et al, 2016).…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…According to Hernández, González, Jiménez and Chaparro (2016), online social learning analytics are a relatively new field so we are only just becoming aware of their possibilities and applications in education. By seeking to analyze what students are doing we may find information about spontaneous interactions, which will provide valuable information about the teaching-learning process.…”
Section: Discussionmentioning
confidence: 99%